2018
DOI: 10.1007/s10532-018-9846-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Dehalococcoides mccartyi species in an autotrophic consortium producing limited acetate

Abstract: The dechlorinating Dehalococcoides mccartyi species requires acetate as carbon source, but little is known on its growth under acetate limiting conditions. In this study, we observed growth and dechlorination of a D. mccartyi-containing mixed consortium in a fixed-carbon-free medium with trichloroethene in the aqueous phase and H/CO in the headspace. Around 4 mM formate was produced by day 40, while acetate was constantly below 0.05 mM. Microbial community analysis of the consortium revealed dominance by D. mc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Acetate excretion was observed previously also in an autotrophic co-culture of D. desulfuricans strain F1 with the non-autotrophic dechlorinating bacterium Dehalococcoides mccartyi. The CO 2 assimilation pathway in Desulfovibrio strain F1 was not investigated, but it produced formate and acetate when grown autotrophically 8 , suggesting that it may use the same pathway as described here for D. desulfuricans strain G11. Further research is needed to shed light on the metabolic and ecologic significance of acetate secretion.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Acetate excretion was observed previously also in an autotrophic co-culture of D. desulfuricans strain F1 with the non-autotrophic dechlorinating bacterium Dehalococcoides mccartyi. The CO 2 assimilation pathway in Desulfovibrio strain F1 was not investigated, but it produced formate and acetate when grown autotrophically 8 , suggesting that it may use the same pathway as described here for D. desulfuricans strain G11. Further research is needed to shed light on the metabolic and ecologic significance of acetate secretion.…”
Section: Resultsmentioning
confidence: 87%
“…The lack of genes for known pathways for CO 2 fixation is also observed in other Desulfovibrio members (Supplementary Data 3 ). Indeed, most Desulfovibrio members do not grow autotrophically with hydrogen, with a few exceptions mentioned above 8 – 10 . The observed autotrophic growth of D. desulfuricans indicates the presence of an unknown CO 2 fixation pathway in this microorganism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond microbial reductive dechlorination, a variety of biological processes (e.g., acidogenesis, hydrogenesis, and methanogens) usually occur synchronously in dechlorinating consortia and at pollution sites, which can affect the rate of microbial reductive dechlorination. ,, The comprehensive analyses conducted in this study revealed that fermentation of organics to acetate and hydrogen can naturally tolerate cocontaminant inhibition. This resilience may arise from the apparent functional redundancy of putative fermenters, thereby contributing to the maintenance of fermentation activity under cocontaminant stress .…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen was measured using a GC instrument (7890A; Agilent) equipped with a thermal conductivity detector and a Varian PLT-5A column (30 m × 0.530 mm × 0.25 μm; Omega Scientific, Singapore). Short-chain volatile fatty acids were measured on an HPLC system (Agilent 1260) equipped with a UV detector (210 nm) and a Rezex ROA-Organic Acid H + (8%) HPLC column (30 cm × 7.8 mm × 8 μm; Phenomenex, Singapore) …”
Section: Methodsmentioning
confidence: 99%